Identifikasi Senyawa Metabolit Sekunder, Uji Antimikroba dan Antioksidan Ekstrak Akar Gantung Hornstedtia Scyphifera Var. Fusiformis Holttum (Sijangkang) - Adlis Santoni; Mai Efdi; Akmel Suhada (Universitas Andalas, 2019)
Hornstedtia scyphifera var. fusiformis Holttum is endemic plant of Zingiberaceae family that distributed in Sumatera. Hornstedtia scyphifera var. fusiformis Holttum contained some secondary metabolite such as phenolic, saponin, triterpenoid and alkaloid. The biological activity of methanol, ethyl acetate, and n-hexane extracts from Hornstedtia scyphifera var. fusiformis Holttum suspended roots was tested for antibacterial and antioxydant activity. Antioxidant activity was analized by DPPH method. The antibacterial activityÂ was tested by used disk difussion method againts Staphylococcus aureus bacteria (gram-positive bacteria) and Escherichia coli (gram-negative bacteria). Almost all of Hornstedtia scyphifera var. fusiformis Holttum suspended roots extract were given antibacterial activity, nonetheless the biggest inhibition zone of Escherichia coli that was inhibited by n-hexane and ethyl acetate extracts which have inhibtion zone 10 mm atÂ concentration 500 mg/L and also againts Staphylococcus aureus, the biggest inhibition by ethyl acetate and n-hexane extracts which have inhibition zone 10.30 mm at concentration 500 mg/L. Among all extracts tested, methanol extract of the possessed moderate free radical scavenging activity with IC50 = 51.89 mg/L.